CAR LICENSE PLATE RECOGNITION BY USING TEMPLATE MATCHING ALGORITHM - Fariza, Mahyan; Termimi Hidayat, Mahyan; Asrani, Lit (2015)
Car License Plate Recognition (CLPR) system is one of the important areas in the intelligent traffic engineering field. CLPR is developed to recognize the car license plate with the implementation of Digital Image Processing (DIP) and Template Matching Algorithm (TMA) approaches by using the MATLAB software. This research works on the offline input images collected by using digital camera. The method of this project is based on template matching where a character is identified by analyzing its shape. Then, the current input character is compared to each template to find either an exact match, or the template with the closest representation of the input character. Experimental results show a high accuracy of the developed CLPR on hundreds random sample images of car license plate in Sarawak.